Kajian Peran Waduk Sebagai Pengendali Kualitas Air Secara Alami - Agung B. Supangat; Paimin Paimin (Forum Geografi, 2007)
In Indonesia it was identified that there were much of polluted stream flow which cause improper consumed water. One of the rivers which has low of water qualities is Citarum River, West Java. However, along the Citarum river, there were built three reservoir dams (Saguling, Cirata and Jatiluhur) that can control the condition of river water regime. Research was conducted in Citarum watershed to determine the role of those reservoirs on water quality control. Seven stations along the river were selected as observation posts of water samples. Based on the observation results it was indicated that water pollutants within Citarum river was very high. However, those pollutants could be purified or reduced by those reservoirs, hence water discharge from the reservoirs has better quality. In the future, deposition of those pollutants within the dam may has negative environment impact. Therefore, to sustain that function of the dam, comprehensive efforts on reducing pollutants from the catchment area is urgently required.